Selected Consumers' Evaluations of Genetically Modified Food Labels - Courtney A. Meyers; Jefferson D. Miller (Journal of Applied Communications, 2007)
Genetically modified (GM) organisms are commonplace in modern agricultural practice. However, polls and surveys have indicated a lack of consumer acceptance of GM ingredients and a desire to see such products identified through the use of labels. In this study, three focus groups composed of consumers in two northwest Arkansas counties evaluated and discussed four genetically modified food labels developed through the use of the Elaboration Likelihood Model, a persuasive communication theory. Findings revealed that participants want labels on food containing GM ingredients. Participants agreed on two features that a GM food label should have: contact information and an identifying symbol. They felt that this label should appear on the front of the package or near the nutrition information. Participants also wanted more consumer education about GM foods and indicated that any label adopted in the future should identify them as such. Further qualitative and quantitative research on consumer preferences regarding GM food labels and the design of such labels is needed.